2016
DOI: 10.1002/aic.15144
|View full text |Cite
|
Sign up to set email alerts
|

Production of benzene, toluene, and xylenes from natural gas via methanol: Process synthesis and global optimization

Abstract: A systematic global optimization‐based process synthesis framework is presented to determine the most profitable processes to produce aromatics from natural gas. Several novel, commercial, and/or competing technologies are modeled within the framework, including methanol‐to‐aromatics, toluene alkylation with methanol, selective toluene disproportionation, and toluene disproportionation and transalkylation with heavy aromatics, among others. We propose a stand‐alone chemicals facility: the main products are aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
103
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(112 citation statements)
references
References 72 publications
0
103
0
3
Order By: Relevance
“…All of the above‐mentioned research reported high yields of p ‐xylene among the aromatic fraction; however, several studies concentrated specifically on this target molecule . Niziolek et al .…”
Section: Methanol To Aromaticsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the above‐mentioned research reported high yields of p ‐xylene among the aromatic fraction; however, several studies concentrated specifically on this target molecule . Niziolek et al .…”
Section: Methanol To Aromaticsmentioning
confidence: 99%
“…All of the above‐mentioned research reported high yields of p ‐xylene among the aromatic fraction; however, several studies concentrated specifically on this target molecule . Niziolek et al . presented a comprehensive techno‐economical study of aromatics refineries that would be feasible and profitable for the production of the BTX (benzene–toluene–xylene) aromatic fraction at greenhouse gas emissions comparable or lower than current fossil‐fuel‐based ones.…”
Section: Methanol To Aromaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high profit of para-xylene production has created incentives for researchers to work on various aspects of the technologies. Among the routes for on-purpose production of para-xylene, toluene alkylation with methanol to para-xylene is promising to become an important process in the chemical industry, because toluene is produced beyond market demand [4,5] and methanol is expected to be extensively obtained from converting coal and natural gas [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…para-Xylene, a critical raw material for polyester manufacture, is the most lucrative petrochemical commodity in three xylene isomers [1][2][3][4]. The high profit of para-xylene production has created incentives for researchers to work on various aspects of the technologies.…”
Section: Introductionmentioning
confidence: 99%